Valuing climate change mitigation applying stated preferences in the presence of uncertainty - Akter, Sonia; Bennett, Jeff.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2012)
Valuing Climate Change Mitigation discusses the role of uncertainty in valuing the benefits of climate change mitigation policies using contingent valuation and choice experiment techniques. It treats climate change using three dimensions of uncertainty: scenario, policy and preference. Conceptual frameworks are advanced to account simultaneously for these various dimensions of uncertainty. The authors then explore the impact of introducing these uncertainties into benefit estimates for the Australian Carbon Pollution Reduction Scheme.
1. Climate change and uncertainty -- 2. Uncertainty and stated preference techniques : a conceptual overview -- 3. Uncertainty and stated preference techniques in practice -- 4. Data -- 5. Public perceptions, understanding and knowledge of climate change -- 6. Climate change uncertainty and contingent valuation welfare estimates -- 7. The role of global cooperation -- 8. Climate change uncertainty and choice experiment welfare estimates -- 9. Determinants of preference uncertainty -- 10. Conclusion.
Includes bibliographical references and index.
Keywords: Climate change mitigation; Electronic books